Ways to Reduce Risks When Building the Digital Economy in Russia. Educational Aspect - Andrey I. Rudskoy; Alexey I. Borovkov; Pavel I. Romanov; Olga V. Kolosova (Высшее образование в России)
А group of authors of Peter the Great St. Petersburg Polytechnic University, working within the framework of the activity of Coordination Council for the Federal Educational and Methodical Associations on education in the field of “Engineering, Technology and Technical Sciences” have undertaken a comprehensive study dedicated to the processes of the digital economy formation. More than two hundred primary sources of reference have been analyzed. Several main groups of risks associated with the transition to global digitalization have been defined and classified. Further research results described in this article allow to characterize the specific features of the occurrence of risks in the Russian Federation and to determine the ways of reducing these risks.In addition to the six groups of risks which are currently possible to arise and which are characteristic of the entire world space, the authors have revealed a number of several additional risks typical only of Russia. One of the key areas in Russia that poses a whole range of various risks is the education system. The authors have analyzed and classified the policies and moves suggested by the researchers and politicians to reduce the likelihood of these specific risks occurrence.The qualitative leap of the educational process in Russia is possible only by means of the formation of some new competence profiles of educational institutions graduates with reference to the digital economy development conditions. The authors have defined seven types of competencies that are relevant for the transition of Russia to the digital economy and developed twelve pilot educational modules necessary for their formation.